Scientific and technical substantiation of the parameters of the radiolocation device for the detection of prohibited items. - Zhantlessov, Y.Zh; Smakova, N.S.; Gruzin, V.V.; Togussov, A.K.; Jussupbekov, T.Kh; Zhantlessov, Zh.Kh. (Eurasian Physical Technical Journal, 2024)
The paper presents a scientific and technical substantiation of the parameters of the radar device, which allows to detect and visualize forbidden objects by means of electromagnetic radiation of the microwave range. A model of a multistatic scheme for measuring waves reflected from an object based on the holographic method is developed. A software complex of simulation modeling of radar device operation has been developed, by means of which reconstructions of object images for different configurations of sparse sensor subsystems of the radar device have been obtained. An optimal configuration of the sparse sensor subsystem was selected by the method of peak signal-to-noise ratio analysis, for which a multi static hologram was modeled and a reconstruction of the metal rod image was generated. The reconstruction of the metal rod image obtained as a result of simulation modeling has a recognizable contour, which confirms the prospect of developing an experimental prototype of a radar device for detecting prohibited objects
Keywords: microwave imaging; holography; multi static array; detection of prohibited items; visualization